On the use of a multi-site ion-exchange model to predictively simulate the adsorption behaviour of strontium and caesium onto French agricultural soils. (September 2021) - Siroux, Brice; Latrille, Christelle; Beaucaire, Catherine; Petcut, Cristina; Tabarant, Michel; Benedetti, Marc F.; Reiller, Pascal E.
Abstract: In case of nuclear accident, 90 Sr and 134, 137 Cs are major radionuclides to account. In previous works (Appl. Geochem. 87, 167; ibid 93, 167), a database of ion-exchange parameters allowing the description of the Sr 2+ and Cs + adsorption on purified illite and smectite was developed for a multi-site ion-exchange (MSIE) model. In this study, the adsorption behaviours of Sr 2+ and Cs + were obtained with <150 μm fractions of French soil samples: a cambisol fluvic, a calcosol, and a cambisol typic. The <2 μm fractions of the soil samples were analysed by X-ray diffraction to estimate their clay minerals proportions that were then approximated to an illite/smectite mixture, in consistency with the CEC of the <150 μm fractions. The database was implemented with K-illite and -smectite parameters to account for the amendment of K + in agricultural soils. The isotherms of Sr 2+ and Cs + on the three soils — at 0.033 mol kgw −1 CaCl2 ( I = 0.1 mol kgw −1 ) and at the pH value of the water equilibrated with the soils — were then compared with simulations obtained using ion-exchange parameters from the database for the MSIE model. This simulation approach, based on the additive adsorption properties between several reactive phases, allowed to describe satisfactorily the adsorption of Sr 2+ and Cs + in most cases. In order to highlight the limiting parameters of the modelling predictive ability, different treatments were made on soil samples. The removal of the natural organic matter did not change significantly the adsorption behaviour of either Sr 2+ or Cs + . The removal of the exchangeable aluminium from the cambisol typic allowed a better simulation of the adsorption isotherm in the case of Sr 2+ . Finally, in the case of the calcosol, the satisfactory modelling of the decrease in adsorption of Sr and Cs using a synthetic CaCl2 pore water with increasing concentrations of KNO3 allowed to verify the robustness of the MSIE model and exchange parameters from the database. Graphical abstract: Image 1 Highlights: Adsorption of Cs and Sr onto 3 representative French agricultural soils was measured. A mixture of illite-smectite was considered for the adsorption simulations. The experimental Kd can be successfully simulated using an existing adsorption database. Natural organic matter did not influence adsorption on these soils. Adsorption in a synthetic porewater was successfully simulated with excess of potassium.